2021
DOI: 10.3390/biom11020258
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Alkaloids Derived from Marine Sponges: A Comprehensive Review

Abstract: Marine sponges (porifera) have proved to be a prolific source of unique bioactive secondary metabolites, among which the alkaloids occupy a special place in terms of unprecedented structures and outstanding biological activities. Identification of active cytotoxic alkaloids extracted from marine animals, particularly sponges, is an important strive, due to lack of knowledge on traditional experiential and ethnopharmacology investigations. In this report, a comprehensive survey of demospongian bioactive alkaloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 101 publications
2
30
0
Order By: Relevance
“…Pyridine derivatives are often part of biomolecules in marine sponges such as alkaloids. [23] Among terpenes, p-cymene, eucalyptol, fenchone, linalool, β-thujone and β-citral were detected in a low percentage. Other compounds such as norisoprenoids, organohalogen compounds and fatty acid derivatives were detected with minor abundance in the total headspace composition.…”
Section: Headspace Composition Of Vocs Isolated By Hs-spmementioning
confidence: 99%
“…Pyridine derivatives are often part of biomolecules in marine sponges such as alkaloids. [23] Among terpenes, p-cymene, eucalyptol, fenchone, linalool, β-thujone and β-citral were detected in a low percentage. Other compounds such as norisoprenoids, organohalogen compounds and fatty acid derivatives were detected with minor abundance in the total headspace composition.…”
Section: Headspace Composition Of Vocs Isolated By Hs-spmementioning
confidence: 99%
“…Sponge genus Aaptos is found in a wide range of ecosystems, including the South China Sea, Japanese, Indonesian, and Caribbean waters [8][9][10][11]. The first discovery was conducted by Nakamura and co-workers from an Okinawan sponge Aaptos aaptos which contain aaptamine, an alkaloidal molecule, in 1981 [12].…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have been revealing the rich diversity of compounds found in marine organisms that can be explored as new drugs for human diseases. Among them, alkaloids stand out as one of the most diverse and largely studied groups of compounds [ 5 , 6 ]. This relatively young field of research is growing fast, and many studies have focused on the accurate identification of chemical structures and evaluation of biological potential in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a recent review compiled around 800 indole alkaloids isolated from algae, microorganisms, sponges, and invertebrate sources [ 5 ]. Moreover, several studies have been carried out to screen and characterize the biological activity of marine alkaloids in vitro against cancer [ 6 ], inflammatory diseases [ 7 ], and parasites [ 8 ], for instance.…”
Section: Introductionmentioning
confidence: 99%